A golden hamster model for human acute Nipah virus infection - Wong, K.T.; Grosjean, I.; Brisson, C.; Blanquier, B.; Fevre-Montange, M.; Bernard, A.; Loth, P.; Georges-Courbot, M.C.; Chevallier, M.; Akaoka, H.; Marianneau, P.; Lam, S.K.; et al. (2003)
A predominantly pig-to-human zoonotic infection caused by the novel Nipah virus emerged recently to cause severe morbidity and mortality in both animals and man. Human autopsy studies showed the pathogenesis to be related to systemic vasculitis that led to widespread thrombotic occlusion and microinfarction in most major organs especially in the central nervous system. There was also evidence of extravascular parenchymal infection, particularly near damaged vessels (Wong KT, Shieh WJ, Kumar S, Norain K, Abdullah W, Guarner J, Goldsmith CS, Chua KB, Lam SK, Tan CT, Goh KJ, Chong HT, Jusoh R, Rollin PE, Ksiazek TG, Zaki SR, Nipah Virus Pathology Working Group: Nipah virus infection: Pathology and pathogenesis of an emerging paramyxoviral zoonosis. Am J Pathol 2002, 161:2153-2167). We describe here a golden hamster (Mesocricetus auratus) model that appears to reproduce the pathology and pathogenesis of acute human Nipah infection. Hamsters infected by intranasal or intraperitoneal routes died within 9 to 29 days or 5 to 9 days, respectively. Pathological lesions were most severe and extensive in the hamster brain. Vasculitis, thrombosis, and more rarely, multinucleated endothelial syncytia, were found in blood vessels of multiple organs. Viral antigen and RNA were localized in both vascular and extravascular tissues including neurons, lung, kidney, and spleen, as demonstrated by immunohistochemistry and in situ hybridization, respectively. Paramyxoviral-type nucleocapsids were identified in neurons and in vessel walls. At the terminal stage of infection, virus and/or viral RNA could be recovered from most solid organs and urine, but not from serum. The golden hamster is proposed as a suitable model for further studies including pathogenesis studies, anti-viral drug testing, and vaccine development against acute Nipah infection.